EXAMINING THE EFFECT OF CSR ON FINANCIAL PERFORMANCE IN CHINA - An Ran; Albattat, Ahmad (International Journal of Multidisciplinary Research and Studies, 2023)
This study focuses on the relationship between CSR and corporate financial performance, mainly discussing the relationship between CSR and ROA, using a sample of listed companies in China to conduct the study and provide relevant suggestions for the subsequent development of the company.